GEEK GRRRLS NEED MODEMS: DISEMBODIEMENT, CYBERLIBERATION AND POSTFEMINISM IN THE 1990S - Houlihan, Rebecca (AoIR Selected Papers of Internet Research, 2026)
This paper analyzes the gendered narratives surrounding the internet created in Australian-based cyberfeminist zine $2 . $2 , a zine that received international recognition, aimed to create an online space and culture for women. It promoted on strategies that empowered individual users and argued for improvements to women's online experiences. However, while presenting itself as an explicitly feminist project, the zine was informed by the 1990s turn towards post-feminism. It dismissed earlier feminist movements and was frequently critical of women who took things said online 'too seriously'.This paper argues that the narratives presented in $2 were attempts to reconcile, somewhat awkwardly, emerging ideas about the liberatory potential of cyberspace and cyberlibertarian ideologies with feminist critique. It positions $2 as a zine that emerged from its historical context, the 1990s turn towards post-feminism, the popularization of internet and web technologies, and ongoing narratives about the relationship between women and technology. $2 played with concepts of embodiment and disembodiment, feminism and post-feminism, online and IRL, and the international and Australian national contexts in which these played out.